2019
DOI: 10.21037/atm.2019.09.65
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of prognosis-related alternative splicing signatures in sarcoma

Abstract: Background: Sarcomas (SARCs) are rare malignant tumors with poor prognosis. Increasing evidence has suggested that aberrant alternative splicing (AS) is strongly associated with tumor initiation and progression.We considered whether survival-related AS events might serve as prognosis predictors and underlying targeted molecules in SARC treatment.Methods: RNA-Seq data of the SARC cohort were downloaded from The Cancer Genome Atlas (TCGA) database. Survival-related AS events were selected by univariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…Variation in AS signatures and cancer-specific AS events could be used as prognostic, predictive, and diagnostic biomarkers for different types of cancers. SpliceSeq analyses have been previously done to generate alterative splicing profiles for different cancers and to identify significant splicing events that can predict cancer prognosis [ 26 , 34 ]. Genome-wide analysis to generate AS profiles of HCC patients followed by identification of significant AS events to predict prognosis has also been done in several studies [ 15 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variation in AS signatures and cancer-specific AS events could be used as prognostic, predictive, and diagnostic biomarkers for different types of cancers. SpliceSeq analyses have been previously done to generate alterative splicing profiles for different cancers and to identify significant splicing events that can predict cancer prognosis [ 26 , 34 ]. Genome-wide analysis to generate AS profiles of HCC patients followed by identification of significant AS events to predict prognosis has also been done in several studies [ 15 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing number of studies that AS plays a crucial role in the oncogenesis and development of cancer. Previous studies reported that AS may accurately evaluate prognostic outcomes in some cancers, including glioblastoma multiforme, colorectal cancer, prostate adenocarcinoma, bladder urothelial carcinoma, gastric cancer and so on [24][25][26]35]. However, the relevant research of cervical squamous cell cancer is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be a credible prognostic biomarker and effective therapeutic target. Previous studies demonstrated that AS event-associated signatures may act as prognostic biomarkers in some cancers, including stomach adenocarcinoma, colorectal cancer, prostate adenocarcinoma, sarcoma, bladder urothelial carcinoma and so on [23][24][25][26][27]. However, comprehensive profiles of alternative splicing events are still scarce in cervical squamous cell cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing number of studies that AS plays a crucial role in the oncogenesis and development of cancer. Previous studies reported that AS may accurately evaluate prognostic outcomes in some cancers, including glioblastoma multiforme, colorectal cancer, prostate adenocarcinoma, bladder urothelial carcinoma, gastric cancer and so on [23,24]. However, the relevant research of cervical squamous cell cancer is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that AS event-associated signatures may act as prognostic biomarkers in some cancers, including stomach adenocarcinoma, colorectal cancer, prostate adenocarcinoma, sarcoma, bladder urothelial carcinoma and so on [21][22][23][24][25]. However, comprehensive pro les of alternative splicing events are still scarce in cervical squamous cell cancer.…”
Section: Introductionmentioning
confidence: 99%